Occupational mobility: how much does caste matter? - Deshpande, Rajeshwari; Palshikar, Suhas (2008)
This paper reports the findings of a study conducted in 2007 on the relationship between caste and occupation in Pune and investigates the patterns of intergenerational occupational mobility across four generations and different caste groups in the city. It finds that while caste is not strongly associated with occupational mobility in general, it is certainly important for upward mobility though the extent of mobility is different among different castes. The maratha-kunbis and dalits are the greatest beneficiaries of upward mobility though there is a difference in the mode of their journey. The Other Backward Classes lag behind these two and some castes among them even show stagnation as far as mobility is concerned. - Reproduced.
Keywords: Caste; Occupational mobility